Bathing in Atopic Dermatitis in Pediatric Age: Why, How and When - Margherita Pagliaro; Luca Pecoraro; Camilla Stefani; Sara Pieropan; Giorgio Piacentini; Angelo Pietrobelli (MDPI AG, 2024)
Atopic dermatitis is a chronic inflammatory skin disease. The treatment plays an important role in influencing the patients' quality of life. The basic management consists of appropriate skin cleansing, including bathing and eventually using bathing additives. Recommendations regarding frequency and duration of bathing, water temperature and usefulness of bathing additives are widely different, often leading to confusion among patients. This review aims to give insights into the best bathing practices and the use of bathing additives in atopic dermatitis in children. Several bathing additives, including bleach baths, commercial baby cleansers, bath baby oils and bath salt, appear to be promising adjunctive therapies for atopic dermatitis due to their anti-inflammatory, anti-bacterial, anti-pruritus and skin barrier repair properties through different mechanisms of action. However, their efficacy and safety are not fully understood in some cases. The usefulness of other bath additives, such as acidic and more natural substances (green tea extracts, pine tar, sodium bicarbonate), is still under investigation. Further studies are needed to determine their optimal use to achieve clinical benefit safely.